Cross-sectional properties of the humeral diaphysis of Paranthropus boisei: Implications for upper limb function. Issue 126 (January 2019) - Lague, Michael R.; Chirchir, Habiba; Green, David J.; Mbua, Emma; Harris, John W.K.; Braun, David R.; Griffin, Nicole L.; Richmond, Brian G.
Abstract: A ∼1.52 Ma adult upper limb skeleton of Paranthropus boisei (KNM-ER 47000) recovered from the Koobi Fora Formation, Kenya (FwJj14E, Area 1A) includes most of the distal half of a right humerus (designated KNM-ER 47000B). Natural transverse fractures through the diaphysis of KNM-ER 470000B provide unobstructed views of cortical bone at two sections typically used for analyzing cross-sectional properties of hominids (i.e., 35% and 50% of humerus length from the distal end). Here we assess cross-sectional properties of KNM-ER 47000B and two other P. boisei humeri (OH 80-10, KNM-ER 739). Cross-sectional properties for P. boisei associated with bending/torsional strength (section moduli) and relative cortical thickness (%CA; percent cortical area) are compared to those reported for nonhuman hominids, AL 288-1 ( Australopithecus afarensis ), and multiple species of fossil and modern Homo . Polar section moduli (Zp ) are assessed relative to a mechanically relevant measure of body size (i.e., the product of mass [M] and humerus length [HL]). At both diaphyseal sections, P. boisei exhibits %CA that is high among extant hominids (both human and nonhuman) and similar to that observed among specimens of Pleistocene Homo . High values for Zp relative to size (M × HL) indicate that P. boisei had humeral bending strength greater than that of modern humans and Neanderthals and similar to that of great apes, A. afarensis, and Homo habilis . Such high humeral strength is consistent with other skeletal features of P. boisei (reviewed here) that suggest routine use of powerful upper limbs for arboreal climbing.